2010
DOI: 10.1176/jnp.2010.22.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain Syndrome Displayed by Malingerers

Abstract: Among 237 patients communicating chronic pain, associated with sensory-motor and "autonomic" displays, qualifying taxonomically for neuropathic pain, there were 16 shown through surveillance to be malingerers. When analyzed through neurological methods, their profile was characteristically atypical. There were no objective equivalents of peripheral or central processes impairing nerve impulse transmission. In absence of medical explanation, all 16 had been adjudicated, by default, the label complex regional pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…3,30 CRPS type II, which presents with an identifiable nerve lesion, may show a decrease in nerve conduction velocity and increased sensorimotor latency on electromyography. 31 Other diagnostic tools for CRPS include bone densitometry, infrared thermography, sweat testing, sympathetic blocks, bedside clinical examination methods, and targeted questionnaires. 1,28,32 MRI has been largely excluded in the CRPS literature because it has been shown to have lower sensitivity and specificity than a three-phase bone scan for CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…3,30 CRPS type II, which presents with an identifiable nerve lesion, may show a decrease in nerve conduction velocity and increased sensorimotor latency on electromyography. 31 Other diagnostic tools for CRPS include bone densitometry, infrared thermography, sweat testing, sympathetic blocks, bedside clinical examination methods, and targeted questionnaires. 1,28,32 MRI has been largely excluded in the CRPS literature because it has been shown to have lower sensitivity and specificity than a three-phase bone scan for CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 237 CRPS patients, surveillance found that 16 of them (about 7%) were malingering [80].…”
Section: Discussionmentioning
confidence: 99%
“…Personal injury insurers require a means to assess the physical and psychological status of their insured, as occurrences of unconscious symptom exaggeration (Dersh, Polatin, Leeman and Gatchel, 2004;Howard, Kishino, Johnston, Worzer and Gatchel, 2010), frank malingering (Greve, Ord, Bianchini and Curtis, 2007;Ochoa and Verdugo, 2010), and over-provision of services (Eisendrath, Rand and Feldman, 1996;Green 2011) exist in personal injury cases. Without independent medical examinations (IMEs), insurers' costs would escalate to a level that would potentially make the provision of coverage unrealistic.…”
Section: Introductionmentioning
confidence: 99%